COMPREHENSIVE ASSESSMENT OF SOIL CONSTAMINATION AT THE SURGIL NATURAL GAS FIELD - Jollibekov, Murat Baxtiyarovich; Tleumuratova, Bibigul Sarybayevna; Urazimbetova, Elzura Pulatovna (SCIENCE and SOCIETY, 2026)
The article examines the results of research on the technogenic pollution of the Surgil gas field soils using local and translocal monitoring, the gradient indication method, GIS technologies, and environmental risk indices. It has been established that the soils are generally slightly polluted, but moderate and strong accumulation of selenium, lead, and copper has been identified. The environmental risk is mostly low, except for cadmium, whose RI index increased to very high by 2022.